Effective charge separation in BiOI/Cu2O composites with enhanced photocatalytic activity. (6th February 2018) - Xia, Yongmei; He, Zuming; Yang, Wei; Bin Tang,; Lu, Yalin; Hu, Kejun; Su, Jiangbin; Li, Xiaoping
Abstract: Novel BiOI/Cu2 O composites were designed and synthesized for the first time by coupling reduction method at low temperature. The samples were characterized by XRD, XPS, SEM, EDS, HRTEM, UV–vis (DRS), FTIR and photo-electro-chemical (PEC) analysis. Results showed that the BiOI/Cu2 O composites consisted of three-dimensional (3D), hierarchical cauliflower-like structure composed of BiOI nanosheet and Cu2 O cubic submicrometer structure, the composite absorption band broadened, and the absorption intensity in the visible region strengthened. And the composites exhibited an excellent photocatalytic performance, which might be attributed to the improvement of the composite absorption and effective charge separation in BiOI/Cu2 O composites. In addition, the possible photocatalytic mechanism was proposed.